2017
DOI: 10.3847/1538-4357/aa9329
|View full text |Cite
|
Sign up to set email alerts
|

A Mote in Andromeda's Disk: A Misidentified Periodic AGN behind M31

Abstract: We identify an object previously thought to be a star in the disk of M31, J0045+41, as a background z ≈ 0.215 AGN seen through a low-absorption region of M31. We present moderate resolution spectroscopy of J0045+41 obtained using GMOS at Gemini-North. The spectrum contains features attributable to the host galaxy. We model the spectrum to estimate the AGN contribution, from which we estimate the luminosity and virial mass of the central engine. Residuals to our fit reveal a blue-shifted component to the broad … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 81 publications
1
17
0
Order By: Relevance
“…This source was investigated in detail by Dorn-Wallenstein et al (2017), who found that it has a spectroscopic redshift, which agrees with our classification as a background galaxy. This source highlights the importance of incorporating data at optical wavelengths to remove background AGN contamination.…”
Section: X-ray Sources In Clusterssupporting
confidence: 84%
“…This source was investigated in detail by Dorn-Wallenstein et al (2017), who found that it has a spectroscopic redshift, which agrees with our classification as a background galaxy. This source highlights the importance of incorporating data at optical wavelengths to remove background AGN contamination.…”
Section: X-ray Sources In Clusterssupporting
confidence: 84%
“…Additional candidates have emerged from the analysis of historical long-baseline light curves of bright AGN (Li et al, 2016;Bon et al, 2016) and the analysis of blazar light curves from the Fermi gamma-ray telescope (Sandrinelli et al, 2016(Sandrinelli et al, , 2018a. Furthermore, Dorn-Wallenstein et al (2017) claimed the detection of a periodic AGN in PTF, which was subsequently disputed by Barth and Stern (2018), who highlight the importance of interpreting correctly the null hypothesis simulation tests and and performing carefully the calculation of the false alarm probability.…”
Section: Photometric Searches For Sub-pc Smbhbsmentioning
confidence: 99%
“…As a result, quasi-periodic variations on timescales ∼ 1/3 the duration of the monitoring almost always appear in lightcurves with this character (Press 1978); because their timescale is a function of an experimental parameter, these quasi-periodicities are spurious, and disappear (to be replaced by longer-term apparent quasi-periodicities) when the data are extended (e.g., as reported by Liu et al (2018)). Statistical analyses based on damped random walk (DRW) models (e.g., Graham et al (2015b); Liu et al (2015); Charisi et al (2016); Dorn-Wallenstein et al (2017)) fail to solve this problem because the DRW model assumes that the fluctuation power spectrum is flat at sufficiently low frequencies. Although this fluctuation power flattening must eventually happen for any finite system, the timescale at which it does is only rarely reached in observed systems.…”
Section: Previous Efforts To Identify Supermassive Binary Black Holesmentioning
confidence: 99%